The sentimental nightmare: The discourse of the scientific and the aesthetic in Rokeya S. Hossain's "Sultana's Dream". Issue 5 (3rd September 2019) - Bhattacharya, Atanu; Hiradhar, Preet
ABSTRACT: This article examines Rokeya Sakhawat Hossain's speculative science fiction story "Sultana's Dream" in the context of science fiction writing in 19th- and 20th-century Bengal. It analyses the story's intersection with a range of discourses and the way this creates a distinctive text. The story is discussed in terms of the key discursive formations that Hossain contends with: that of the "women's question" (with an emphasis on the Muslim woman's question); the nature of the violence that produces a male-dominated state; and the possibility of a scientific–aesthetic intervention capable of countering such male violence. The article argues that Hossain's speculative science fiction, by portraying the liberatory potential of a transformed scientific state apparatus, produces a model of a feminist Utopia which is not grounded simply in gender, but also in the possibility of a state based on a rational aesthetic.